2018
DOI: 10.1007/s00726-018-2544-4
|View full text |Cite
|
Sign up to set email alerts
|

Ameliorative effects of taurine against diabetes: a review

Abstract: Diets in rats and humans have shown promising results. Taurine improved glucagon activity, promoted glycemic stability, modified glucose levels, successfully addressed hyperglycemia via advanced glycation end-product control, improved insulin secretion and had a beneficial effect on insulin resistance. Taurine treatment performed well against oxidative stress in brain, increased the secretion of required hormones and protected against neuropathy, retinopathy and nephropathy in diabetes compared with the contro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 53 publications
(25 citation statements)
references
References 187 publications
1
16
0
3
Order By: Relevance
“…Significant increases in taurine levels have been consistently observed after intake of glucose or sugar-sweetened beverages in previous studies [ 43 , 44 ]. Indeed, an in vivo study showed that taurine could improve glucose homeostasis by reducing the synthesis of AGEs or preventing mitochondrial dysfunction in β-cells [ 45 ]. Of note, the increase in levels of another metabolite, 5′-methylthioadenosine, could be explained by activation of adenosylmethionine synthase upon glucose intake and upregulated conversion of S-adenosylmethionine to 5′-methylthioadenosine [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…Significant increases in taurine levels have been consistently observed after intake of glucose or sugar-sweetened beverages in previous studies [ 43 , 44 ]. Indeed, an in vivo study showed that taurine could improve glucose homeostasis by reducing the synthesis of AGEs or preventing mitochondrial dysfunction in β-cells [ 45 ]. Of note, the increase in levels of another metabolite, 5′-methylthioadenosine, could be explained by activation of adenosylmethionine synthase upon glucose intake and upregulated conversion of S-adenosylmethionine to 5′-methylthioadenosine [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…The beneficial effects of taurine have been demonstrated in many diseases such as decreased serum low-density lipoprotein, decreased progression of atherosclerosis, and protection against ischemiareperfusion injury of the myocardium (Schaffer and Kim 2018;Xu et al 2008;Abebe and Mozaffari 2011;Lambert et al 2015;De Luca et al 2015). Besides, the beneficial effects of taurine in diabetic cardiovascular complications are well documented (Franconi et al 1995(Franconi et al , 2004Inam-U-Llah et al 2018;Lewis et al 2014;Manna et al 2013;Tappia et al 2011Tappia et al , 2013Tappia et al , 2018Turan 2010). It has been suggested that taurine increases the high-energy phosphate content of the heart (Schaffer and Kim 2018;Schaffer et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, recent results demonstrate that Tau depletion could impair ammonia detoxification in mouse livers, associated with oxidative stress and senescence [ 29 ]. On the other hand, dietary supplementation of Tau was shown to be associated with a reduction in the risk of various diseases, including diabetes [ 30 , 31 ], metabolic syndrome [ 32 ], skeletal muscle disorders [ 33 ], retinal degeneration [ 23 ], atherosclerosis [ 34 ], liver diseases [ 35 ], central nervous system disorders [ 36 ], etc.…”
Section: Taurine Essentiality and Requirementmentioning
confidence: 99%